Construction of Self‐Activated Nanoreactors for Cascade Catalytic Anti‐Biofilm Therapy Based on H2O2 Self‐Generation and Switch‐On NO Release. (10th February 2022) - Shi, Yuting; Cao, Yufei; Cheng, Ju; Yu, Wenwen; Liu, Mingsheng; Yin, Juanjuan; Huang, Congshu; Liang, Xiaoqin; Zhou, Haicun; Liu, Hongbin; Yang, Zheng; Fang, Yu; et al.
Abstract: The traditional treatment for bacterial infections is the use of antibiotics, but the overuse of antibiotics can lead to the formation of multidrug‐resistant bacteria, and eventually lead to the formation of biofilms, which can resist the attack of the host immune system and the penetration of antibiotics in biofilms. Although biofilm‐targeted and stimulus‐responsive antibiotic delivery nanocarriers are available, the drugs that can be delivered is extremely limited. Therefore, an amphiphilic supramolecule Arg‐CD‐AcMH is constructed via host–guest interactions between β‐CD‐terminated arginine (Arg‐CD) and ferrocene‐terminated acetal‐modified maltoheptaose. The amphiphilic supramolecule Arg‐CD‐AcMH can self‐assemble with glucoamylase and glucose oxidase in aqueous solution to form spherical nanoparticles through hydrophilic–hydrophobic and electrostatic interactions. These nanoparticles can respond to the micro‐environment in the biofilm and selectively increase the level of H2 O2 in the biofilm through the cascading catalytic effect of enzymes based on the self‐supply glucose, thus providing conditions for the release of anti‐biofilm active drug nitric oxide. Abstract : A self‐activated nanoreactor is developed for bacterial‐infected wound healing. The nanoreactors could respond to the microenvironment in the biofilm, and selectively increase the level of H2 O2 in the biofilm through the cascading catalytic effect of enzymes based on the self‐supply glucose, thus providing conditions for the release of anti‐biofilm active drug nitric oxide.